Effect of evacetrapib on cardiovascular outcomes in patients with high-risk cardiovascular disease - Aronow, Wilbert S. (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Reducing serum low-density lipoprotein (LDL) cholesterol by statins has been shown to reduce cardiovascular events and mortality in secondary and primary prevention trials (1-3). Further reduction of serum LDL cholesterol in patients after an acute coronary syndrome treated with statins by ezetimibe (4) and in patients with cardiovascular disease treated with statins by the proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor evolocumab (5) have been demonstrated to further reduce cardiovascular events .